Interaction of pharmaceutical & personal care products (PPCPs) and endocrine disrupting contaminants (EDCs) with microbial communities in South African wastewater treatment works and environmental waters - Archer, Edward (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.